2020
DOI: 10.1097/aog.0000000000003876
|View full text |Cite
|
Sign up to set email alerts
|

Abortion Policies in U.S. Teaching Hospitals

Abstract: OBJECTIVE: To evaluate the prevalence and features of policies regulating abortion in U.S. teaching hospitals. METHODS: In this mixed-methods study, we conducted a national survey of obstetrics and gynecology teaching hospitals (2015–2016) and qualitative interviews (2014 and 2017) with directors at obstetrics and gynecology residency programs. We asked participants about hospital regulations on abortion and their perceptions of the nature and enforceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 14 publications
1
18
1
1
Order By: Relevance
“…Prior fi ndings from these study data demonstrated that a majority of teaching hospitals have institutional policies that regulate abortion on the basis of gestation and reason for needing the procedure, with abortions at later gestations or those considered "elective" being more severely regulated. 13 Similarly, in the current analyses, approximately half of respondents agreed that their colleagues resist abortion provision because of personal beliefs about acceptable gestational limits and reasons. This type of policing is in line with Kimport et al ' s notion of "stratifi ed legitimacy"; physicians make choices about which abortions to provide, for whom and for what reasons that refl ect society ' s judgments about women ' s reproductive behavior.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Prior fi ndings from these study data demonstrated that a majority of teaching hospitals have institutional policies that regulate abortion on the basis of gestation and reason for needing the procedure, with abortions at later gestations or those considered "elective" being more severely regulated. 13 Similarly, in the current analyses, approximately half of respondents agreed that their colleagues resist abortion provision because of personal beliefs about acceptable gestational limits and reasons. This type of policing is in line with Kimport et al ' s notion of "stratifi ed legitimacy"; physicians make choices about which abortions to provide, for whom and for what reasons that refl ect society ' s judgments about women ' s reproductive behavior.…”
Section: Discussionmentioning
confidence: 60%
“…[4][5][6][7][8][9][10][11] Abortion in hospitals is highly regulated. [4][5][6]12,13 Published fi ndings based on data from the current study demonstrated that more than half of U.S. obstetrics-gynecology teaching hospitals have policies that limit abortion beyond the requirements of state law. 13 Similarly, a 2002-2003 national survey found that 34% of obstetrician-gynecologists practiced in a hospital that restricted abortion provision.…”
Section: Interprofessional Abortion Opposition: a National Survey Andmentioning
confidence: 66%
See 3 more Smart Citations